Neuroimaging Changes and Treatment Outcome of Tubercular Meningitis- Experiences 22 Cases in a Tertiary Care Center - Kundu, Gopen Kumar; Zahan, Gulsan-Ara; Sarker, Mohammad Arbab; Dola, Farah Naz (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Tuberculous meningitis (TBM) is caused by Mycobacterium tuberculosis (M. tuberculosis) and is the most common form of central nervous system (CNS) tuberculosis (TB).The prevalence of TB meningitis remains largely underestimated because clinical manifestations are nonspecific in early stages of the disease. Prompt diagnosis is critical for initiating appropriate therapy, facilitating measures to prevent dissemination of this highly contagious disease and to combat fatal complication in children Aims: To evaluate the role of neuroimaging changes and treatment outcome of tubercular meningitis. Methods: This prospective hospital-based cohort study was conducted in Department of Paediatric Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during January 2022 to December 2022. Children age belonged to 1 month to 10 year diagnosed as TBM during study period were enrolled in this study. Detailed history, clinical examination, CSF analysis and other relevant investigations were done. Data were recorded in standard questionnaire. Statistical analyses of the results were obtained by using window-based computer software devised with Statistical Packages for Social Sciences (SPSS-22). Results: Total 22 diagnosed case of TBM was enrolled and evaluated. Among them two third (63.63%) children were in 5-10 year age group. Male (59%) were outnumbered than female (36.36 %).Male female ratio was 1.6:1. More than half (59%) of patients came from urban area. All of the patients were vaccinated. Cent percent (100%) patients were presented with fever followed by headache (77.27%), sign of meningeal irritation (54.54%), vomiting (54.54%) and seizures (50%). Most common complication was hemiparesis (45.45%) followed by cranial nerve palsy (40.90%), visual problem (9.09%) and hydrocephalus (4.54%). Abnormal neuroimaging changes were found in 100% cases. Common findings were hydrocephalus (40.90%), tubercloma (36.36%), basilar enhancement (18.18%), Benign enlargement of subdural space & cerebellar hyperintensity (9%) and thalamic infract was present in 4.54% cases. Anti TB and steroid treatment were given in 100% cases and among them18.18% cases were required shunt procedure. More than one-third cases (40.90%) were completely normal without any no sequelae. Among abnormal sequelae found in two third (59%) cases. Speech impairment (36.36%) was most common followed by GDD (18.18%), hemiparesis (13.63%), quadriparesis (9.09%) and epilepsy in 9.09% cases. Conclusion: In our study all children of TBM were presented with fever followed by other predominant clinical features headache, vomiting, seizures and sign of meningeal irritation. Abnormal neuroimaging changes were found in all cases. Common findings were basilar enhancement, hydrocephalus, tubercloma, benign enlargement of subdural space & cerebellar hyper intensity and thalamic infract. After treatment more than one-third cases were completely normal without any no sequelae. J Bangladesh Coll Phys Surg 2024; 42: 214-218